PRODUCT ADVERTISEMENT AND BRAND EQUITY EFFECT TO CONSUMER BRAND CHOICE IN MANADO - Maramis, Gabriella; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Company is using advertising as a media to offered products, so the product could be known and sold well in the market place. That is why advertising is made as attractive as possible, so that sometimes can be too extravagate, and ignoring the psychological, sociological, ecological, and aesthetic target audience or product being advertised. The aim of this research analysis is using multiple regression and causal research as a tool to gather data and analysis. This study collected 105 respondents data sample of population of people in Manado. The conclusion of this study is the influence of product advertisement and brand image on consumer brand choice, simultaneously and partially are significant. The recommendation of this research result is to increase brand equity the company should expand the brand engagement to the consumer and give more promotion. Â  Keywords: product advertising, brand equity, consumer brand choice